Dendritic cadmium sulfide nanometer material and preparation method thereof
Dendritic cadmium sulfide nanomaterials are synthesized via a controlled hydrothermal process, addressing the limitations of existing sensors by enhancing sensitivity and selectivity to target gases through adjustable morphology and large surface area.
Patent Information
- Application Number
- CN202411299903.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
AI Technical Summary
Existing semiconductor gas sensors, particularly those using metal oxide semiconductors, suffer from long response recovery times, poor stability, and limited responsiveness, with cadmium sulfide (CdS) needing improved morphology for enhanced gas sensing performance.
A method for synthesizing dendritic cadmium sulfide using ethylene glycol and water as hydrothermal solvents, with cadmium chloride and thiourea as reactants, and polyvinylpyrrolidone (PVP) as a surfactant to control morphology, followed by hydrothermal reaction and centrifugation to produce nanomaterials with adjustable leaf thickness.
The method produces dendritic cadmium sulfide nanomaterials with uniform morphology and large leaf area, enhancing sensitivity and selectivity to target gases, suitable for large-scale production, and improving response values to gases like methanol, formaldehyde, and isopropanol.
Smart Images

Figure CN119160931A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano materials, and relates to a method for preparing a cadmium sulfide nano material, in particular to a method for preparing dendritic cadmium sulfide, and can control the thickness of its leaves. Background Art
[0002] Industrial production inevitably involves some toxic and harmful gases, so there are some dangerous hidden dangers in this process. However, if you want to discover similar situations in a timely and effective manner, researchers need to develop high-performance gas sensors. Gas sensors are used in all aspects of life and production practice. The exploitation of fossil energy involves the monitoring of hydrogen sulfide, carbon monoxide and various hydrocarbon gases; in the civilian field, the monitoring of gases such as methanol (CH3OH), ethanol (C2H5OH), coal gas and liquefied natural gas is related to the personal and property safety of the people, so the monitoring of these gases is very necessary; in automobile and industrial production, the monitoring of gases such as hydrogen sulfide (H2S), sulfur dioxide (SO2), carbon monoxide (CO) and carbon dioxide (CO2) in the exhaust gas is of great significance to ensure air quality.
[0003] The detection principle of semiconductor gas sensors is: when semiconductor materials are placed in the atmosphere to be measured, gas molecules will come into contact with the material, and the resistance or work function of the material will change. By detecting these changes with certain devices, the gas can be indirectly detected. Semiconductor sensors include resistive and non-resistive types. For resistive gas sensors, if the reaction between gas molecules and materials only occurs on the surface of the material, then the material is a surface-controlled material; if the reaction between gas molecules and materials occurs in the body of the material, then the material is a body-controlled material.
[0004] In the field of gas sensors, metal oxide semiconductors have been studied in depth by scientific researchers for a long time in the past, but there are also some problems in their performance that need to be solved, such as long response recovery time, poor stability and short life. Therefore, in recent years, people have begun to pay attention to the application of metal sulfide semiconductors in gas detection. As a representative of metal sulfides, CdS has been widely used in ultraviolet, photoelectric detection and other fields, and has also been reported in the field of gas sensors. CdS has a fast response recovery time in gas detection, but there is still room for improvement in responsiveness. In terms of gas sensors, the morphology of the material can affect its specific surface area and other properties, thereby affecting its performance in the gas detection process. At present, cadmium sulfide with various morphologies has been synthesized, including rods, spheres, and wires. Cadmium sulfide with different morphologies has a great influence on its gas sensing performance. The development of cadmium sulfide with new morphologies to improve its gas sensing performance has always been a research hotspot. Summary of the invention
[0005] In order to solve the above problems in the prior art, the present invention provides a method for synthesizing a new dendritic cadmium sulfide morphology. The main technical solutions adopted by the present invention include:
[0006] S1: Ethylene glycol and water are used as reaction solvents in a volume ratio of 1:1. Cadmium chloride and thiourea are added as reactants in a ratio of Cd:S=1:1, and a surfactant PVP is added to control the morphology by changing the PVP content.
[0007] S2: After stirring evenly, transfer to a high-pressure reactor for hydrothermal reaction at a temperature of 180-220°C for 18-26 hours. After the reaction is completed, collect by centrifugation, and wash and dry the product.
[0008] In a preferred embodiment, in S1, the solvent used is a mixture of deionized water and ethylene glycol in a ratio of 1:1.
[0009] In a preferred embodiment S1, the cadmium chloride solution and the thiourea solution are prepared by dissolving cadmium chloride and thiourea in a mixture of deionized water and ethylene glycol and mixing them uniformly, wherein the concentration of the cadmium chloride solution is 0.01-0.04 g / mL, the concentration of the thiourea solution is 0.005-0.008 g / mL, and the PVP content is 0.01-0.05 g / mL.
[0010] In a preferred embodiment S1, when the content of PVP added to the mixed solution is 0.01-0.02 g / mL, a dendritic cadmium sulfide with thicker leaves can be obtained; when the content of PVP is 0.03-0.05 g / mL, a dendritic cadmium sulfide with thinner leaves can be obtained.
[0011] In a preferred embodiment, in S2, after sufficient stirring and mixing, the stirred solution is transferred into a high-pressure reactor for hydrothermal reaction at 180-220° C. for 18-26 h.
[0012] In a preferred embodiment, in S2, the reaction system to obtain the precipitate is centrifuged in a centrifuge at a speed of 3000-4000 rpm for 8-10 min, the supernatant is removed, and the precipitate is collected and placed in a drying oven at 50-60° C. for 8-10 h.
[0013] According to the method of the invention, dendritic cadmium sulfide nanomaterials with good morphology and uniform product distribution can be obtained.
[0014] In a second aspect, the present invention also provides a dendritic cadmium sulfide nanomaterial prepared by the preparation method.
[0015] In a third aspect, the present invention further provides a use of the dendritic cadmium sulfide nanomaterial in preparing a semiconductor gas sensor.
[0016] The beneficial effects of the present invention are:
[0017] Compared with the prior art, the present invention has the following characteristics: 1. Water and ethylene glycol are selected as hydrothermal solvents and the proportions are made to successfully prepare a thin layer of dendritic CdS with a large leaf area, uniform morphology and uniform distribution; 2. The purpose of adjustable morphology is achieved by changing the amount of PVP added, and the CdS nanomaterials whose morphology is regulated by PVP can significantly improve their maximum response value to the target gas; 3. The hydrothermal reaction is carried out at relatively high temperature and pressure, and nanoparticles can be obtained by reactions that cannot be carried out under normal conditions; 4. The preparation process of the present invention is simple, the cost is low, the product is easy to collect, and it is suitable for large-scale production. 5. The dendritic cadmium sulfide nanomaterial prepared by the present invention shows a strong response to a variety of target gases (including but not limited to methanol, formaldehyde, isopropanol, ethanol, etc., especially isopropanol), and significantly improves its response to the target gas. 6. The dendritic cadmium sulfide nanomaterial prepared by the present invention has high sensitivity and good selectivity to the target gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the XRD spectrum of the product prepared in Example 1 of this patent;
[0019] Figure 2 This is a SEM photo of the dendritic cadmium sulfide prepared in Example 1 of this patent;
[0020] Figure 3 This is a TEM photo of the dendritic cadmium sulfide prepared in Example 1 of this patent;
[0021] Figure 4 This is a SEM photo of the long rod-shaped cadmium sulfide prepared in Comparative Example 1 of this patent;
[0022] Figure 5 This is a SEM photo of a thin layer of dendritic cadmium sulfide prepared in Comparative Example 2 of this patent;
[0023] Figure 6 This is a gas-sensing performance diagram of a thin layer of dendritic cadmium sulfide prepared in comparative example 2 of this patent;
[0024] Figure 7 This is a graph showing the gas-sensitive response performance of the thin layer of dendritic cadmium sulfide prepared in comparative example 2 of this patent to different gases;
[0025] Figure 8 This is a SEM photograph of the dendritic cadmium sulfide prepared in Example 1 of this patent. DETAILED DESCRIPTION
[0026] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation methods.
[0027] This embodiment proposes a new method for preparing a thin layer of dendrite cadmium sulfide, and controls the thickness of the dendrite cadmium sulfide blade by controlling the amount of PVP added. The preparation method of the nanomaterial includes the following steps:
[0028] S1: Ethylene glycol and water are used as reaction solvents in a volume ratio of 1:1. Add reactants cadmium chloride and thiourea in a molar ratio of Cd:S=1:1, and add surfactant PVP to control the morphology by changing the PVP content.
[0029] S2: After stirring evenly, transfer to a high-pressure reactor for hydrothermal reaction at a temperature of 180-220°C for 18-26 hours. After the reaction is completed, collect by centrifugation, and wash and dry the product.
[0030] Specifically, S1 includes the following steps:
[0031] S1.1: Prepare a mixed solution of ethylene glycol and water in a ratio of 1:1 and a total volume of 60 mL.
[0032] S1.2: Add a certain amount of cadmium chloride crystals (CdCl2·2.5H2O) and thiourea to the prepared ethylene glycol aqueous solution. Finally, add a certain amount of PVP to the mixed solution.
[0033] S2.1: Stir the mixed solution evenly and continue stirring for 1 hour after all substances are dissolved.
[0034] S2.2: After stirring, the solution is transferred to a stainless steel high-pressure reactor for hydrothermal reaction.
[0035] S2.3: Wash, centrifuge and dry the product.
[0036] In step S1.2, the concentration of the cadmium chloride solution is 0.01-0.04 g / mL, for example, the concentration is any one of 0.01 g / mL, 0.02 g / mL, 0.03 g / mL, and 0.04 g / mL. The concentration of the thiourea solution is 0.005-0.008 g / mL, for example, the concentration is any one of 0.04 g / mL, 0.1 g / mL, 0.005 g / mL, 0.006 g / mL, and 0.008 g / mL. The content of PVP is 0.01-0.05 g / mL, for example, 0.01 g / mL, 0.03 g / mL, 0.05 g / mL, etc. can be selected.
[0037] In step S2.2, the hydrothermal reaction temperature is 180-220° C., preferably any one of 180° C., 190° C., 200° C., 210° C., and 220° C. The hydrothermal time is 18-26 h, preferably any one of 18 h, 20 h, 22 h, 24 h, and 26 h.
[0038] In step S2.2, the centrifuge speed, centrifugal separation time, drying temperature and time can be any value within the preferred range.
[0039] The present invention is further illustrated by the following examples.
[0040] Example 1
[0041] Example 1 proposes a preparation method of a dendritic cadmium sulfide nanomaterial, which specifically includes the following steps:
[0042] S1,
[0043] S1.1: Prepare a mixed solution of ethylene glycol and water, using 30 mL of deionized water and 30 mL of ethylene glycol.
[0044] S1.2: Weigh cadmium chloride crystals (CdCl2·2.5H2O) and thiourea. The concentration of cadmium sulfide is 0.02g / mL, the concentration of thiourea is 0.006g / mL, and finally add 0.01g of PVP.
[0045] S2,
[0046] S2.1: Stir the mixed solution evenly using a magnetic stirrer. After all substances are dissolved, continue stirring for 1 hour.
[0047] S2.2: After stirring, the solution was transferred to a stainless steel high-pressure reactor for hydrothermal reaction. The reactor volume was 100 mL, the hydrothermal temperature was 200°C, and the hydrothermal time was 22 h.
[0048] S2.3: After the reaction is completed, cool to room temperature, wash the product with deionized water and alcohol, collect the precipitate by centrifugation, and finally dry at 60°C for 12h.
[0049] Figure 1 The XRD spectrum of dendrite cadmium sulfide is given. It can be seen from the figure that there are no impurity peaks, indicating that the synthesized product is relatively pure. Figure 2 Figure 3 and Figure 8 The SEM and TEM photos of the dendritic cadmium sulfide in Example 1 are respectively given, and the morphology is uniform, the distribution is even, and the leaves are relatively thick.
[0050] Comparative Example 1
[0051] The influence of solvent selection on product morphology was investigated.
[0052] S1,
[0053] S1.1: The hydrothermal solvent is selected to be all deionized water, using 60 mL.
[0054] S1.2: Weigh cadmium chloride crystals (CdCl2·2.5H2O) and thiourea. The concentration of cadmium sulfide is 0.02g / mL, the concentration of thiourea is 0.006g / mL, and finally add 0.01g of PVP.
[0055] S2,
[0056] S2.1: Stir the mixed solution evenly using a magnetic stirrer. After all substances are dissolved, continue stirring for 1 hour.
[0057] S2.2: After stirring, the solution was transferred to a stainless steel high-pressure reactor for hydrothermal reaction. The reactor volume was 100 mL, the hydrothermal temperature was 200°C, and the hydrothermal time was 22 h.
[0058] S2.3: After the reaction is completed, cool to room temperature, wash the product with deionized water and alcohol, collect the precipitate by centrifugation, and finally dry at 60°C for 12h.
[0059] like Figure 4 As shown, when no ethylene glycol is added to the hydrothermal solvent, its SEM morphology appears to be a long bread-like shape, and no dendrite-like morphology is formed. Only when ethylene glycol is added as a solvent can the growth of dendrites be facilitated.
[0060] Comparative Example 2
[0061] The effect of PVP addition on product morphology was studied.
[0062] S1,
[0063] S1.1: Prepare a mixed solution of ethylene glycol and water, using 30 mL of deionized water and 30 mL of ethylene glycol.
[0064] S1.2: Weigh cadmium chloride crystals (CdCl2·2.5H2O) and thiourea. The concentration of cadmium sulfide is 0.02g / mL, the concentration of thiourea is 0.006g / mL, and finally add 0.05g of PVP.
[0065] S2,
[0066] S2.1: Stir the mixed solution evenly using a magnetic stirrer. After all substances are dissolved, continue stirring for 1 hour.
[0067] S2.2: After stirring, the solution was transferred to a stainless steel high-pressure reactor for hydrothermal reaction. The reactor volume was 100 mL, the hydrothermal temperature was 200°C, and the hydrothermal time was 22 h.
[0068] S2.3: After the reaction is completed, cool to room temperature and remove the product
[0069] like Figure 5 As shown, it can be seen that with the increase of PVP addition, the leaf orientation of dendritic cadmium sulfide becomes thinner and thinner, and the leaf area becomes larger, and the leaves converge into bundles.
[0070] Application Examples
[0071] Application Example 1
[0072] The WS-30A gas sensor test system produced by Henan Weisheng Company was used to test the gas sensing performance of the CdS nanoparticles prepared in this patent to 100ppm ethanol gas at different temperatures. As a comparison, the gas sensing performance of commercial CdS nanoparticles was tested. CdS nanoparticles are n-type semiconductors. When the semiconductor material is exposed to air, oxygen molecules in the air are adsorbed on the surface of the material to become adsorbed oxygen. When heated, the adsorbed oxygen captures free electrons from the CdS conduction band to become O - , O 2- This results in a decrease in the carrier concentration in the material, an increase in the barrier of electron transmission in the electron depletion layer structure, and an increase in the sensor resistance. When the reducing gas contacts the surface of the CdS nanoparticles, it reacts with the adsorbed oxygen and releases the electrons bound by the oxygen anions, thereby reducing the sensor resistance. The change in resistance can be used to obtain the optimal operating temperature, sensitivity, selectivity and other data of the CdS nanoparticle gas sensor.
[0073] The best working temperature of gas sensors made of various materials is as follows: Figure 6 As shown in the figure, the optimal working temperature for preparing CdS nanoparticles in this patent is 275°C, and the highest response value (Response = R air / R gas , R air (or R a ) represents the resistance of the gas sensor in air, R gas (or R g ) represents the resistance of the gas sensor in the test gas) reached 6.53, which is much higher than commercial CdS nanoparticles. The reason why the gas-sensing performance of CdS nanoparticles prepared in this patent is greater than that of commercial CdS is that the prepared iron oxide is nanoscale and has a larger specific surface area, which is conducive to the adsorption and diffusion of gas to the surface of the material, so that it shows a high responsiveness to the target gas.
[0074] like Figure 7As shown in the figure, the dendritic CdS with morphology controlled by PVP shows responsiveness to a variety of organic gases (including but not limited to acetone, pyridine, xylene, n-butylamine, methanol, formaldehyde, isopropanol, ethanol, etc.), among which the response to isopropanol is the highest, reaching 9.44; it also shows good response to methanol, formaldehyde and ethanol, with response values reaching about 5.20 to 6.50. The different responses of CdS to different gases are related to its specific electronic composition.
[0075] Table 1 Response to different gases
[0076]
[0077] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific embodiments of the present invention without paying creative work, and these methods will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a dendritic cadmium sulfide nanomaterial, characterized in that: Includes steps: S1: Using ethylene glycol and water as reaction solvents, adding reactants cadmium chloride and thiourea, the addition ratio of which is Cd:S=1:1, and adding surfactant polyvinylpyrrolidone PVP, and controlling the morphology by changing the PVP content; S2: After stirring evenly, transfer to a high-pressure reactor for hydrothermal reaction at a reaction temperature of 180-220°C for a reaction time of 18-26h; after the reaction is completed, collect by centrifugation, and wash and dry the product.
2. The preparation method according to claim 1, characterized in that: In S1, the reaction solvent is deionized water and ethylene glycol, with a volume ratio of 1:
1.
3. The preparation method according to claim 1, characterized in that: In S1, cadmium chloride and thiourea are respectively dissolved in a mixture of deionized water and ethylene glycol and mixed thoroughly to obtain a mixed solution; wherein the concentration of cadmium chloride is 0.01-0.04 g / mL, and the concentration of thiourea is 0.005-0.008 g / mL.
4. The preparation method according to claim 1 or 3, characterized in that: In S1, the PVP content in the mixed solution is 0.01-0.05 g / mL, preferably 0.01-0.02 g / mL or 0.03-0.05 g / mL.
5. The preparation method according to claim 1, characterized in that: In S2, after sufficient stirring and mixing, the stirred solution is transferred into a high-pressure reactor for hydrothermal reaction at 180-220° C. for 18-26 hours.
6. The preparation method according to claim 1, characterized in that: In S2, the reaction system with the precipitate is centrifuged in a centrifuge at a speed of 3000-4000 rpm for 8-10 min, the supernatant is removed, and the precipitate is collected; and the precipitate is placed in a drying oven at 50-60° C. and dried for 8-10 h.
7. A dendritic cadmium sulfide nanomaterial prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the dendritic cadmium sulfide nanomaterial according to claim 7 in preparing a semiconductor gas sensor.
